HIV-1 Protease Uses Bi-Specific S2/S2′ Subsites to Optimize Cleavage of Two Classes of Target Sites. Issue 24 (7th December 2018) - Potempa, Marc; Lee, Sook-Kyung; Kurt Yilmaz, Nese; Nalivaika, Ellen A.; Rogers, Amy; Spielvogel, Ean; Carter, Charles W.; Schiffer, Celia A.; Swanstrom, Ronald
Abstract: Retroviral proteases (PRs) have a unique specificity that allows cleavage of sites with or without a P1′ proline. A P1′ proline is required at the MA/CA cleavage site due to its role in a post-cleavage conformational change in the capsid protein. However, the HIV-1 PR prefers to have large hydrophobic amino acids flanking the scissile bond, suggesting that PR recognizes two different classes of substrate sequences. We analyzed the cleavage rate of over 150 combinations of six different HIV-1 cleavage sites to explore rate determinants of cleavage. We found that cleavage rates are strongly influenced by the two amino acids flanking the amino acids at the scissile bond (P2 –P1/P1′–P2′ ), with two complementary sets of rules. When P1′ is proline, the P2 side chain interacts with a polar region in the S2 subsite of the PR, while the P2′ amino acid interacts with a hydrophobic region of the S2′ subsite. When P1′ is not proline, the orientations of the P2 and P2′ side chains with respect to the scissile bond are reversed; P2 residues interact with a hydrophobic face of the S2 subsite, while the P2′ amino acid usually engages hydrophilic amino acids in the S2′ subsite. These results reveal that the HIV-1 PR has evolved bi-functional S2 and S2′ subsites to accommodate the steric effects imposed by a P1′ proline on the orientation of P2 and P2′ substrate side chains. These results also suggest a new strategy for inhibitor design to engage the multiple specificities in these subsites. Graphical abstract: Highlights: The HIV-1 protease is essential for viral replication and a major drug target. The protease is unique in cleaving next to hydrophobic amino acids or next to proline. By cleaving many substrates, we identified two optimal cleavage site sequences. P1′ proline reorients the P2 and P2′ substrate side chains in the S2 and S2′ subsites. The bi-specific S2 and S2′ subsites could be targets for more complex inhibitors.